An Improved Method for Estimating the Strength of Jointed Rock Mass Using Drilling Technology. (16th August 2022) - Zhang, Yong; Li, Peng; Liu, Fengyin
Abstract : During underground excavations for civil and mining engineering purposes, the variations in mechanical properties of jointed rock mass are important, especially for the design of underground structures. The unreasonable evaluation of strength properties for rock masses can lead to the structure instability of underground construct, which subsequently causes collapse accidents in underground engineering and poses a serious threat to the structures safety. Rock mass classification system is an effective method for determining the strength parameters for rock masses. Firstly, the existing approaches for determining the strength parameters of rock masses are reviewed using classification systems such as the joint factor, jointing index methods, rock mass rating (RMR), Q-system (Q), geological strength index (GSI), and rock quality designation (RQD). Since in some cases, rock quality designation (RQD) is the only information available, a comparative study with other methods then is conducted to verify the limitation and deficiencies of RQD method. On this basis, a newly developed method from RQD classification system based on drilling special energy is established to estimate the rock mass strength. Finally, the developed method is applied in the tunnel engineering in the Daheba hydropower station in Hanjiang to the Weihe River project of China, and the results are compared with those from the previous works. The in situ test results show that the developed method can give appropriate values compared to various suggested relationships from RMR, Q, and GSI. The results can be treated as an important design reference for the prevention and treatment of surrounding rock instability and underground excavations in the Daheba hydropower station.